(untitled) (Journal of Oriental Studies, 2021)
The article discusses the language features of Temirnamе, written in Arabic letters. Chagatai is literary language which is used by nearly all Turkish societies who lived in Central Asia in the other words east side of the Caspian Sea from the beginning of 15. century to 20. century. It is known that there are a lot of works which is written in this literary language. One of them is a manuscript named Ās̱ār-ı Dāstān-ı Emı̇̄r Timür Köregen. This work is registered in Almaty Academy of Sciences (Ғылым Ордасы) in Section of Manuscripts and number of 367. The cover of manuscript was made of heavy leather and it is well preserved. Text is size of 15.7 x 25,8 cm. and made of 96 leaves (192 pages) and there are 17 lines in each page. It was written in font type of ta’lik and vowel point was not used without a few words. The page numbers were not revealed. The name of the text was written in the beginning of first page with red-ink. The events were seperated from each other by titles of el-ḳıṣṣa which is penned with red-ink. There is not an accurate information about author/ interpreter or copyist of this work which is told about life of Emir Timür as an anecdote. The works like Zafer-nâme, Acâibü’l-makdûr fî nevâibi Tîmûr offered historical proofs for major part of the events that has been told in the text, but different from these works, in the work that was examined by us, the manner of telling is epical. When we consider ortographical and language properties of this work, it is understood that the work was written in the era of Postclassical Chagatai Turkish. In this notice, we will introduce the manuscript of Ās̱ār-ı Dāstān-ı Emı̇̄r Timür Köregen and reveal its language properties. Key words: Turcology, linguistics, Chagatai Turkish, Timür, Timür-nâme.